Marine natural products. Issue 6 (24th February 2022) - Carroll, Anthony R.; Copp, Brent R.; Davis, Rohan A.; Keyzers, Robert A.; Prinsep, Michèle R.
Abstract : A comprehensive review of 1407 new MNPs including turbinmicin, a potent antifungal lead isolated from a marine bacterium. Abstract : Covering: 2020 This review covers the literature published in 2020 for marine natural products (MNPs), with 757 citations (747 for the period January to December 2020) referring to compounds isolated from marine microorganisms and phytoplankton, green, brown and red algae, sponges, cnidarians, bryozoans, molluscs, tunicates, echinoderms, mangroves and other intertidal plants and microorganisms. The emphasis is on new compounds (1407 in 420 papers for 2020), together with the relevant biological activities, source organisms and country of origin. Pertinent reviews, biosynthetic studies, first syntheses, and syntheses that led to the revision of structures or stereochemistries, have been included. A meta analysis of bioactivity data relating to new MNPs reported over the last five years is also presented.